Fatal spirorchiidosis in European pond turtles (Emys orbicularis) in Switzerland. (April 2022) - Schönbächler, Katja; Olias, Philipp; Richard, Olivia K.; Origgi, Francesco C.; Dervas, Eva; Hoby, Stefan; Basso, Walter; Berenguer Veiga, Inês
Abstract: Infections with intravascular digenean trematodes of the Spirorchiidae family (spirorchiidoses) are of great conservation concern both in marine and freshwater turtles due to their pathogenic potential. Between 2014 and 2021, Spirorchis sp. infections associated with granulomatous inflammation and sudden death were detected in European pond turtles ( Emys orbicularis ) from three conservation breeding facilities in Switzerland. Blood fluke eggs associated with lesions were found in the intestine, spleen, testis, skeletal musculature, heart, kidneys, stomach, pancreas, liver, lung, and meninges from nine pond turtles submitted for necropsy and in the intestinal content from five of these animals. Two novel polymerase chain reactions (PCRs) targeting the 28S ribosomal RNA gene and the ITS2 region and subsequent sequencing revealed 100% nucleotide identity with a Spirorchis sp. previously isolated from an Escambia map turtle ( Graptemys ernsti ) in the USA. Our findings suggest a spill-over event secondary to direct or indirect contact with invasive North American turtle species in Switzerland. We describe the clinical, haematological, ultrasonographical, endoscopical, parasitological, pathological, and molecular findings associated with spirorchiid blood fluke infections of the Spirorchis genus in E. orbicularis, as well as the biosecurity measures that were developed to prevent the spread of this parasite among breeding and highly endangered free-ranging E. orbicularis populations in Switzerland. Graphical abstract: Image 1 Highlights: Spirorchiidosis was recorded in three Swiss Emys orbicularis breeding facilities. Spirorchis sp . infection was detected by parasitological and molecular methods. Spill-over events from invasive American turtle species are suspected. Biosecurity measures are essential to avoid Spirorchis sp. spread into wild populations.